The Children's Book of Cars, Trains, Boats and Planes - Allen, Kenneth (Octopus Books Ltd : London, 1978)
Explores the history of travel and transportation, looking at the technological development of boats and ships, trains, automobiles, airplanes, and jet aircraft.
Keywords: Vehicles History